Pengaruh Investasi dan Indeks Pembangunan Manusia (IPM) Terhadap Pertumbuhan Ekonomi di Provinsi Jawa Timur - Najah, Safinatun; Hayatul Millah; Yeni Kartikawati (DPPM Universitas Pelita Bangsa, 2025)
The goal of this study is to see how East Java Province's GDP has increased in connection to investment and the Human Development Index (IPM). This research focuses on economic development, investment, and IPM figures collected from East Java Province between 2019 and 2023. The sample of secondary data includes the entire province of East Java. This study uses a quantitative approach, including t-tests, F-tests, coefficient of determination tests, and multiple linear regression analysis. We used SPSS version 23 to examine the data. This study demonstrated no significant impact of investment or IPM on economic growth in East Java Province, either alone or in combination.